The economics of airport operations - Peoples, James; Bitzan, John D. (Emerald Publishing Limited, 2017)
Airports serve an essential role in domestic and international travel, facilitating the origination, termination, and connections of air flights. Airport services enhance regional, national, and global connections, increasing the mobility of people worldwide and enhancing local and regional economies. Although there is a large amount of literature that examines airline costs and productivity, consumer welfare from air travel, and the influence of economic regulation of airline services, there is much less literature that examines airports. This is important, as airport operations play a critical role in influencing airline travel. This volume examines the role that airports play in economic development and land values, the regulation and economic efficiency of airports, airport pricing and competition, and the role played by airports in influencing airline operations and networks.
Prelims -- Introduction -- Light-handed regulation of airport services: an alternative approach to direct regulation? -- Two-sidedness and welfare neutrality in airport concessions -- Estimation of allocative efficiency in airports for a pre-privatization period -- Airport - airline arrangements: an interpretive review of industry practices and recent studies -- Airport and airline relationship of multiple functional structures -- Pricing of airport operations -- The cost structure of the airport industry: methodological issues and empirical evidence -- Airport charges - interactions between airlines and airports -- Spatial evolution of airports: a new geographical economics perspective -- The heterogeneous impact of airports on population and employment growth in cities -- The effect of international airports on commercial property values: case studies of Toronto, Ontario, Canada and Vancouver, BC, Canada -- Airport congestion and airline network structure -- Low-cost carriers and airports: a complex relationship -- Benchmarking worldwide airport connectivity with demand data: global hub competition, new players, and the hidden potential of self-connectivity -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Transportation -- Aviation -- General; Economics; Airports -- Economic aspects